2006
DOI: 10.1016/j.cub.2006.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Proliferation in Drosophila Imaginal Discs Requires Dronc-Dependent p53 Activity

Abstract: How cell death and cell proliferation are coordinated during development and after stress is a fundamental question that is critical for an understanding of growth regulation. Our data suggest that dp53 may carry out an ancestral function that promotes animal survival through the coordination of responses leading to compensatory growth after tissue damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
244
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(260 citation statements)
references
References 46 publications
16
244
0
Order By: Relevance
“…Johnston and colleagues 7 have proposed that Dp53 gene promotes the expression of mitogens, such as Wg, which is required for apoptosisinduced proliferation. However, the specific roles of the Dp53 and DDNp53 isoforms in activating Wg have not been defined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Johnston and colleagues 7 have proposed that Dp53 gene promotes the expression of mitogens, such as Wg, which is required for apoptosisinduced proliferation. However, the specific roles of the Dp53 and DDNp53 isoforms in activating Wg have not been defined.…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila p53 gene is proposed to act in a feedback loop to self-amplify and promote apoptosis-induced proliferation. 7,34 Therefore, we wanted to examine how the endogenous p53 gene contributes to the observed overexpression phenotype. We produced DDNp53 or Dp53 in p53-null flies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, Dronc activity is required for compensatory proliferation and functions to promote expression of the mitogens Wingless (Wg) and Decapentaplegic (Dpp) to promote proliferation of neighboring cells. [108][109][110] The effector caspases Drice and Dcp-1 can also induce compensatory proliferation in differentiating eye tissue, by activation of the Hedgehog signaling pathway. 106 These studies demonstrated critical roles for caspases in coordinating both cell death and proliferation during development and regeneration, and provided the first in vivo evidence for a nonapoptotic function for an initiator-apoptotic caspase.…”
Section: Caspases In Cell Proliferation and Tissue Regenerationmentioning
confidence: 99%